HOW NEW IS "NEW HERMENEUTIC"? - Legrand, L. (Journal of Dharma, 1980)
Neapolis, the New Town of the Greek colonists of the 6th century B.C., has now become Naples, one of the most ancient cities of the Old Continent. It is the fate of everything "new", slowly to age and soon to become outdated. The so-called "NeW" Hermeneutic has now been with us for quite some time. In fact, it would be time to start preparing its sashtipoorthi, its sixtieth anniversary, if we go with the commonly accepted view that its first manifesto and official appearance in biblical studies was Karl Barth’s Preface to the second edition of his commentary on Romans, in September 1921. Sixty years is quite a long period in the fast moving world of today. Can a sixty years old movement of ideas still be called "new" ? Does not the fact that this label is still in currency simply demonstrate that biblical scholarhip moves at a pace markedly slower than the World it lives in? Is not" new hermeneutic" an old lady still playing the coquette when the time has come for her to prepare her will and quit the scene?